Seleksi Beberapa Kombinasi Persilangan Padi untuk Ketahanan Terhadap Keracunan Aluminium - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The study aimed to select some F rice hybrids for Al toxicity resistance was conducted in Al toxicity soil, Jasinga, Bogor, West Java, on the dry-season of 2003. The experiment consisted of 30 Fi hybrids (Indica x Javanica) and 4 check varieties such as IR64 (susceptible), Hawara Bunar (resistant), Kapuas (resistant), and Batanghari (resistant) to Al toxicity soil, was designed using Augmented Design. Data indicated that, 3 F, rice hybrids namely IR68888A/Kapuas, IR58025A/Mendawak, and IR68885A/Kapuas yielded around 1 t/ha over the best check variety (Batanghari, 5.13 t/ha). Yield of these 3 F1 rice hybrids mentioned above was 6.25